Magnetic Nanoadsorbent Functionalized with Aminophosphonic Acid for Ndiii Ion Extraction from Aqueous Media - Venegas-Yazigi, D; Venegas-Yazigi, D; Gutierrez-Cutino, M; Gutierrez-Cutino, M (Elsevier B.V., 2023)
The adsorption performance of a new magnetic nanoadsorbent of Nd3+ was investigated. First, the nanoadsorbent was synthesized by chemical coprecipitation, and covered with a silica layer by the sol–gel method to obtain the silica-coated magnetic nanoparticles (MNP@SiO2). Subsequently, it was functionalized with nitrilotris(methylene)triphosphonic acid (NTMP), obtaining the goal aminophosphonic-functionalized nanoadsorbent (MNP@SiO2-NTMP). The functionalized nanoadsorbent was characterized using TEM, XRD, VSM, TGA, ATR-FTIR, EDS, and zeta potential measurements, confirming its nanoscale size, superparamagnetic behavior, and the presence of surface amino-phosphonic groups. The influence of different operational parameters on neodymium adsorption was investigated. The highest adsorption capacity of neodymium(III) was approximately 18 mg·g−1 at pH 6.8, using an adsorbent dose of 1 g·L-1, a neodymium concentration of 100 mg·L-1, and a contact time of 15 min at room temperature. The neodymium(III) adsorption onto MNP@SiO2-NTMP followed a pseudosecond-order model, suggesting chemisorption mechanisms as the rate-limiting step. Batch experimental results showed that Nd3+ adsorption onto MNP@SiO2-NTMP was independent of the ionic strength, indicating the formation of inner-sphere surface complexes. Furthermore, the adsorption thermodynamic analyses suggested that neodymium adsorption was exothermic, entropy decreasing, and more favorable at low temperatures. The best adsorbent regeneration and neodymium desorption from the loaded adsorbent was achieved using acidic solutions of H2SO4, exhibiting excellent adsorbent reusability throughout the four adsorption–desorption cycles. The MNP@SiO2-NTMP was an effective adsorbent material for extracting neodymium(III) from dilute aqueous solutions. Therefore, it is expected that MNP@SiO2-NTMP can potentially be used in more sustainable recovery methods of neodymium from secondary sources, for example, from leaching solutions of NdFeB magnet scraps. © 2023 Elsevier B.V.